Pengaruh Gaya Kepemimpinan, Ketrampilan Komunikasi Dan Kotbah Terhadap Komitmen Organisasional Jemaat Di GKI Dasa Surabaya - Frederich Oscar Lontoh (Jurnal Teologi dan Pelayanan Kerusso, 2017)
This research is titled The Influence of Leadership Style, Communication Competence and Sermon on Organizational Commitment at GKI Darmo Satelit Surabaya. The purpose of research is to identify and analyze whether Leadership Style, Communication Competence and Sermon have influence on the organizational commitment of congregation at GKI Darmo Satelit Surabaya. The population in this study were all congregation at GKI Darmo Satelit Surabaya. Samples of this study are 100 respondent. Through sampling stratified Random techniques. These influence was measured using Pearson correlation coefficient and multiple regression analysis, t-test and analysis of variance. Descriptive analysis were taken to analyze organizational commitment levels according to demographic groups. The hypothesis in this study are the Leadership Style, Communication Competence and Sermon have positive and significant on organizational commitment. The results showed that collectively, there are positive and significant correlation among Leadership Style, Communication Competence and Sermon on Organizational Commitment at GKI Darmo Satelit Surabaya 71,1%. It means that 71,1% of organizational commitment in GKI Darmo Satelit Surabaya influenced by Leadership style, communication competence and sermon and the other 28,9% by others. All of the variable partially have significant correlation to Organizational Commitment.